2018
DOI: 10.5897/ajmr2018.8892
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Escherichia coli, Salmonella and Pasteurella from holding grounds of live-bird markets at Addis Ababa, Ethiopia

Abstract: A cross-sectional study was conducted to isolate and identify of Escherchia coli, Pastuerella multocida, Salmonella gallinarum and Salmonella pullorum from the holding grounds of five purposively selected Addis Ababa live bird markets from November 2016 to May 2017 using bacterial culture, grams staining and biochemical testing. A total of 90 pooled fecal samples were collected as both deep (35) (bottom layer of the feces) and surface (55) (top layer of the feces). The specimens were inoculated directly into b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…These differences in the isolation rates may be owing to the differences in the number of samples, the age of birds, the geographic regions, the isolation methods, and previous medication. The cultural morphology, Gram staining characters and biochemical reactions of suspected E. coli isolates were similar to those reported by Hadiujjaman et al (2016), Surra et al (2018) and Ibrahim et al (2019). Moreover, the serological identification results of this study revealed that the main serotypes of the isolated E. coli were O78 and O1.…”
Section: Discussionsupporting
confidence: 89%
“…These differences in the isolation rates may be owing to the differences in the number of samples, the age of birds, the geographic regions, the isolation methods, and previous medication. The cultural morphology, Gram staining characters and biochemical reactions of suspected E. coli isolates were similar to those reported by Hadiujjaman et al (2016), Surra et al (2018) and Ibrahim et al (2019). Moreover, the serological identification results of this study revealed that the main serotypes of the isolated E. coli were O78 and O1.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, microbiological contaminants, including Escherichia coli (E. coli O157:H7) are available on the body, and personal closure of the worker results in meat contamination; these findings are consistent with those of. 40 , 41 …”
Section: Discussionmentioning
confidence: 99%